Simplified method for determining fracture toughness of two dental ceramics - Potchaman Sinavarat (2018)
© 2016, Japanese Society for Dental Materials and Devices. All rights reserved. This study compared the fracture toughness values (KIC), which were derived from simplified techniques: the indentation fracture (IF), the indentation strength (IS), and fractographic approach to that from a standard testing using surface cracks in flexure (SCF). Forty bar specimens, twenty IPS Empress® Esthetic and twenty IPS e.max®Ceram were prepared. Ten specimens in each material were tested by IF technique, IS technique and fractographic approach, and additional 10 specimens were tested by the SCF technique. This study showed that the mean KICderived from fractographic approach were not significantly different from that of the SCF in both materials (p>0.05) whereas the mean KICfrom indentation techniques rarely agreed with those of the standard technique. The KICdetermination is sensitive to the methods used that affect accuracy. Consequently, test selection should be based on a sound understanding and inherent limitations of each technique.